Three-Dimensional Corrective Osteotomy for Malunited Diaphyseal Forearm Fractures Using Custom-Made Surgical Guides Based on Computer Simulation - Miyake, Junichi (JBJS Essent Surg Tech, 2012)
INTRODUCTION: Three-dimensional corrective osteotomy with use of custom-made surgical guides based on computer simulation can provide a good outcome for patients with a malunited diaphyseal forearm fracture. STEP 1: CREATE COMPUTER BONE MODELS FROM CT DATA: Obtain CT data of both forearms, and create computer models of the bones from CT data. [Figure: see text] STEP 2: EVALUATE 3D DEFORMITY: Evaluate the 3D deformity by comparing the affected bone with the mirror image of the contralateral, normal bone. [Figure: see text] STEP 3: PLAN 3D CORRECTIVE OSTEOTOMY: Simulate the 3D corrective osteotomy on the basis of information obtained from the deformity evaluation. [Figure: see text] [Figure: see text] STEP 4: DESIGN CUSTOM-MADE SURGICAL GUIDES: Design custom-made surgical guides to reproduce the preoperative simulation during the actual surgery. [Figure: see text] STEP 5: OPERATIVE SETUP: Manufacture custom-made surgical guides to reproduce the preoperative simulation during the actual surgery. [Figure: see text] STEP 6: PERFORM 3D OSTEOTOMY USING CUSTOM-MADE OSTEOTOMY GUIDES: Perform the osteotomy using the custom-made osteotomy guides and achieve anatomical correction using the reduction guides. [Figure: see text] RESULTS: In our series of twenty patients, the average radiographic deformity angle preoperatively was 21° (range, 12° to 35°) compared with that of the normal arm; this improved to 1° (range, 0° to 4°) postoperatively [Figure: see text] WHAT TO WATCH FOR: Indications Contraindications Pitfalls & Challenges